2016
DOI: 10.1111/jbi.12710
|View full text |Cite
|
Sign up to set email alerts
|

The role of wet‐zone fragmentation in shaping biodiversity patterns in peninsular India: insights from the caecilian amphibianGegeneophis

Abstract: Aim Indian biodiversity is concentrated in the wet zone, which is disjunctly distributed in the north-east and in the peninsular Western and Eastern Ghats. The Eastern Ghats region is smaller and less well explored biologically and the affinities and origins of its biota poorly understood. Our aim was to assess whether divergence between east and west lineages might have been caused by fragmentation of the wet zone during Pleistocene climatic fluctuations, by Late Miocene wet-zone contraction or by more ancien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…R. beddomei prefer evergreen forests (Bates and Harrison, 1997;Wordley et al, 2015), which might explain their positive correlation of RF with humidity. R. lepidus colonized peninsular India about 1.5 Ma (Quaternary period), when aridification effects were strong and rainfall was pulsed (Kale et al, 2003;Gower et al, 2016). Rhinolophids of the R. pusillus sub-group (to which R. lepidus belongs), underwent major range expansions in this period (Dejtaradol, 2009;Jiang et al, 2010b (Csorba et al, 2003;Dejtaradol, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…R. beddomei prefer evergreen forests (Bates and Harrison, 1997;Wordley et al, 2015), which might explain their positive correlation of RF with humidity. R. lepidus colonized peninsular India about 1.5 Ma (Quaternary period), when aridification effects were strong and rainfall was pulsed (Kale et al, 2003;Gower et al, 2016). Rhinolophids of the R. pusillus sub-group (to which R. lepidus belongs), underwent major range expansions in this period (Dejtaradol, 2009;Jiang et al, 2010b (Csorba et al, 2003;Dejtaradol, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic relationships among Seychelles caecilians remain incompletely resolved, including identi cation of the closest extant relative of H. rostratus [38,55]. However, analyses of a previously published dataset [25] using the same methods reported in that study found that, applying nine different calibration strategies, mean estimated ages of splits among sampled extant species of Hypogeophis and Grandisonia are in the range of 16.4 -27.9…”
Section: Introductionmentioning
confidence: 86%
“…The granitic islands are of continental origin [16], and are mountain-top remnants of the largely submerged Seychelles Microcontinent ["Seychellea" of 17] that once formed part of the supercontinent Gondwanaland. These ancient remnants were isolated by the separation from Africa of a landmass [Indigascar of 18] consisting of Madagascar, Seychelles and India [19][20][21][22][23][24]; with the Seychelles becoming fully separated approximately 65 -62 Ma [24,25]. Much of the Seychelles Microcontinent, comprising the exposed (ca.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we focus on Hypogeophis rostratus (54) because it is the most widespread endemic amphibian in the Seychelles, occurring on 10 of the granitic islands (53). Although the phylogenetic relationships among Seychelles caecilians remain unresolved (52,55), an available estimate dates the split between H. rostratus and its possible closest extant relative at ca.19 Ma (56). Hypogeophis rostratus resides in a variety of habitats and elevations and is often found in high abundance in human altered habitat such as coconut plantations and gardens (pers.…”
Section: Introductionmentioning
confidence: 99%